Involvement of inflammatory responses in the brain to the onset of major depressive disorder due to stress exposure - Miyata, Shingo; Ishino, Yugo; Shimizu, Shoko; Tohyama, Masaya (Frontiers in Aging Neuroscience, 2022)
Major depressive disorder is a multifactorial disease affected by several environmental factors. Although several potential onset hypotheses have been identified, the molecular mechanisms underlying the pathogenesis of this disorder remain unclear. Several recent studies have suggested that among many environmental factors, inflammation and immune abnormalities in the brain or the peripheral tissues are associated with the onset of major depressive disorders. Furthermore, several stress-related hypotheses have been proposed to explain the onset of major depressive disorders. Thus, inflammation or immune abnormalities can be considered stress responses that occur within the brain or other tissues and are regarded as one of the mechanisms underlying the stress hypothesis of major depressive disorders. Therefore, we introduce several current advances in inflammation studies in the brain that might be related to the pathophysiology of major depressive disorder due to stress exposure in this review.